2019
DOI: 10.1002/alr.22389
|View full text |Cite
|
Sign up to set email alerts
|

Associations among air pollutants, grass pollens, and daily number of grass pollen allergen‐positive patients: a longitudinal study from 2012 to 2016

Abstract: Background Grass pollen is the most prevalent sensitizing aeroallergen to cause respiratory allergies in northern China. Air pollutants have a substantial effect on respiratory health and some pollens. This study aimed to investigate relationships among airborne grass pollen, air pollutants and allergic diseases, in order to determine their effects on patients with grass pollen allergies in Beijing, China, during the period from 2013 to 2016. Methods Data regarding autumnal grass pollens and air pollutants mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…2 Indeed, recent studies from China have demonstrated that the concentrations of particulate matter <2.5 μm (PM2.5) and PM10 in the air were closely related to the incidence of AR, 3,4 and additionally significantly impacted the type and concentration of pollen. 5 Evidence indicates that nasal epithelial cells play an integral role in innate and adaptive immune responses to diverse environmental pollutants and allergens by synthesizing and releasing numerous inflammatory cytokines. Studies investigating the effect of exposure to PM2.5 have shown that this pollutant may lead to loss of barrier of function in nasal epithelial cells through decreased expression of tight junction (TJ) proteins, 6,7 and lead to increased expression and release of inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin 8 (IL-8), IL-6, IL-1β, and eotaxin from airway epithelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Indeed, recent studies from China have demonstrated that the concentrations of particulate matter <2.5 μm (PM2.5) and PM10 in the air were closely related to the incidence of AR, 3,4 and additionally significantly impacted the type and concentration of pollen. 5 Evidence indicates that nasal epithelial cells play an integral role in innate and adaptive immune responses to diverse environmental pollutants and allergens by synthesizing and releasing numerous inflammatory cytokines. Studies investigating the effect of exposure to PM2.5 have shown that this pollutant may lead to loss of barrier of function in nasal epithelial cells through decreased expression of tight junction (TJ) proteins, 6,7 and lead to increased expression and release of inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin 8 (IL-8), IL-6, IL-1β, and eotaxin from airway epithelial cells.…”
mentioning
confidence: 99%
“…The prevalence of AR has markedly increased during the past 30 years, especially in developing countries, with increasing evidence showing that air pollution is likely to be associated with increased AR mobidity 2 . Indeed, recent studies from China have demonstrated that the concentrations of particulate matter <2.5 µm (PM2.5) and PM10 in the air were closely related to the incidence of AR, 3,4 and additionally significantly impacted the type and concentration of pollen 5 …”
mentioning
confidence: 99%
“…There are noticeable regional differences in the incidence of allergic diseases in China, and there are also noticeable regional differences in the types of allergens. The main allergens in Beijing are pollen ( Figure 1 ), 2 , 3 and the main allergens in Guangzhou are dust mites ( Figure 1 ). 4 This study analyzed the two keywords “allergic rhinitis” and “allergic conjunctivitis” from January 1, 2014 to June 30, 2020, and found that the search trend of the keyword “allergic rhinitis” in the whole country was consistent with that in Beijing but significantly different from that in Guangzhou ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“… 1 Allergic rhinitis (AR) and allergic conjunctivitis (AC) are common allergic diseases in China. Pollen are the main allergens in Beijing ( Figure 1 ), 2 , 3 a modern city in northern China, and dust mites in Guangzhou ( Figure 1 ), 4 a modern city in southern China. The clinical symptoms of AR include itchy nose, stuffy nose, sneezing, and runny nose.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is growing to be a global concern, particularly as it plays a major role in people's health, especially in respiratory systems. Ouyang et al . carried out a longitudinal study from 2012 to 2016 in Beijing, China, and report that the daily number of grass pollen–positive patients was significantly associated with the peak period of grass pollens, as well as the air pollutants sulfur dioxide (SO 2 ) and nitrogen oxides (NO x ).…”
mentioning
confidence: 99%